PERANCANGAN FONT MOTIF LATAR BATIK "MO' RAMO'" SEBAGAI PROMOSI KAB. PAMEKASAN - Islam, Ach. Farhannur (AKSA: Jurnal Desain Komunikasi Visual, 2025)
Batik is an invaluable cultural heritage of Indonesia, with each region offering distinct motifs. Among these is the Mo' Ramo' motif, a hallmark of Pamekasan, Madura, symbolizing strength and resolve. Despite its historical and philosophical significance, the production of Mo' Ramo' batik has declined due to time-intensive crafting processes and high costs, risking its extinction. This study aims to preserve the Mo' Ramo' motif through digital innovation by developing a font inspired by its unique patterns. The Design Thinking framework, encompassing empathize, define, ideate, prototype, and test phases, was employed to ensure user-centered outcomes. The results showcase a font named "Akarramo," which seamlessly integrates Mo' Ramo' elements while maintaining legibility and visual appeal. Testing indicated its potential for use in promotional materials and as a tool for cultural preservation. This innovative approach demonstrates the viability of typography as a medium for safeguarding traditional art forms while enhancing public awareness of Pamekasan's cultural heritage. The findings provide a foundation for further explorations of batik-based typography, fostering a sustainable fusion of tradition and modernity.